Look at What's Wrong With Me! (Out of Print) - Derrick Hamaoka (Association of American Medical Colleges, 2008)
Abstract This Flash-based presentation presents a simulated case of an outpatient who presents with body image issues. The case takes the participant through the initial history, mental status examination, differential diagnosis, and discussion of the case. The case contains web-based feedback questions; ongoing results are stored, and participants can see how their responses compared to colleagues. In our clerkship, the students must see a patient with a somatoform disorder, which can be challenging to accomplish in the 6-week timeframe. This offers an opportunity for them to meet this requirement.